2017
DOI: 10.1186/s13014-017-0791-2
|View full text |Cite
|
Sign up to set email alerts
|

Subventricular zones: new key targets for glioblastoma treatment

Abstract: BackgroundWe aimed to identify subventricular zone (SVZ)-related prognostic factors of survival and patterns of recurrence among patients with glioblastoma.MethodsForty-three patients with primary diagnosed glioblastoma treated in our Cancer Center between 2006 and 2010 were identified. All patients received surgical resection, followed by temozolomide-based chemoradiation. Ipsilateral (iSVZ), contralateral (cSVZ) and bilateral (bSVZ) SVZs were retrospectively segmented and radiation dose-volume histograms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…10,15,25 There are data suggesting that inclusion of the SVZ in radiotherapy planning has a positive effect on outcome. 9,16,22 Furthermore, the increased peritumoral perfusion of ventricle-contacting GBMs could be targeted with neurosurgery. Using rCBV maps in neurosurgical planning of ventricle-contacting GBMs could possibly change the extent of resection, thereby improving outcome for patients with these tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,15,25 There are data suggesting that inclusion of the SVZ in radiotherapy planning has a positive effect on outcome. 9,16,22 Furthermore, the increased peritumoral perfusion of ventricle-contacting GBMs could be targeted with neurosurgery. Using rCBV maps in neurosurgical planning of ventricle-contacting GBMs could possibly change the extent of resection, thereby improving outcome for patients with these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We identified the SVZ as a 5-mm margin surrounding the ventricles corresponding to earlier definitions of the SVZ used by others. 9,16,22 Ventricle masks were created in GeoS (Springer-Verlag) from the preoperative contrast-enhanced T1-weighted images. Further processing was done in MATLAB (MathWorks Inc.).…”
Section: Regions Of Interestmentioning
confidence: 99%
“…As loss of RND1 is involved in GSCs migration from PVZ+ tumors, known to be more aggressive than PVZ– tumors [ 19 21 ], we tested whether RND1 gene expression could be correlated with glioblastoma prognosis. First, we analyzed RND1 expression by RT-qPCR in normal brain tissues, in several glioblastoma cell lines and in GSCs established in our laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…In relation with tumor heterogeneity, clinical data, including ours, demonstrates that relapses in glioblastoma after radio-chemotherapy are more aggressive in tumors contacting the PVZ (PVZ+) than in PVZ– tumors. PVZ+ patients progress quicker and have a decreased overall survival compared to those with tumors not contacting the PVZ (PVZ–) [ 19 21 ]. Moreover, we have also recently shown that contact of glioblastoma with PVZ was an independent prognosis factor of shorter progressive free survival after re-irradiation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective study of 43 patients with glioblastoma [24] was conducted to identify SVZ related prognostic factors for survival and recurrence patterns. Results on multivariate analysis showed contact to SVZ, as well as reduced bSVZ radiation dose coverage (V20Gy <84%), might be independent poor prognostic factors for time to progression (7 months versus 5.2 months, p = 0.017).…”
Section: Evidence Supporting Improved Survival With Higher Svz and Pvmentioning
confidence: 99%